Average Error: 0.2 → 0.2
Time: 8.8s
Precision: 64
$\left(t \cdot t\right) \cdot \left(3 - 2 \cdot t\right)$
$t \cdot \left(t \cdot \left(3 - 2 \cdot t\right)\right)$
\left(t \cdot t\right) \cdot \left(3 - 2 \cdot t\right)
t \cdot \left(t \cdot \left(3 - 2 \cdot t\right)\right)
double f(double t) {
double r1078924 = t;
double r1078925 = r1078924 * r1078924;
double r1078926 = 3.0;
double r1078927 = 2.0;
double r1078928 = r1078927 * r1078924;
double r1078929 = r1078926 - r1078928;
double r1078930 = r1078925 * r1078929;
return r1078930;
}


double f(double t) {
double r1078931 = t;
double r1078932 = 3.0;
double r1078933 = 2.0;
double r1078934 = r1078933 * r1078931;
double r1078935 = r1078932 - r1078934;
double r1078936 = r1078931 * r1078935;
double r1078937 = r1078931 * r1078936;
return r1078937;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.2

$\left(t \cdot t\right) \cdot \left(3 - 2 \cdot t\right)$
2. Using strategy rm
3. Applied associate-*l*0.2

$\leadsto \color{blue}{t \cdot \left(t \cdot \left(3 - 2 \cdot t\right)\right)}$
4. Final simplification0.2

$\leadsto t \cdot \left(t \cdot \left(3 - 2 \cdot t\right)\right)$

# Reproduce

herbie shell --seed 1
(FPCore (t)
:name "t*t*(3-2*t)"
:precision binary64
(* (* t t) (- 3 (* 2 t))))